CHILDREN'S CHARACTER EDUCATION THROUGH BONDHAN PAYUNG DANCE - Prasetiyo, Ari (International Review of Humanities Studies, 2024)
Education, especially children's character education, is very important. Education can be carried out in formal and non-formal educational institutions. One of the learning media that can be used is through traditional cultural arts.The traditional Javanese cultural art that is the object of this research is the Bondhan Payung dance, which is taught at Sanggar Ayodya Pala Cibinong and PPKB FIB UI. The selection of Bondhan Payung dance as the object of research with the consideration that in Bondhan Payung dance contained teaching values that are important for teaching children's character.This research uses a qualitative approach by applying the concept of triangulation. Data as well as information are based on observations of the practice process in class, interviews with trainers and parents of students. The results of this research found a positive influence of character training through Bondhan Payung dance media on children's characters.